Craniofacial Trauma and Vascular Injury - Bernath, Megan M.; Mathew, Sunu; Kovoor, Jerry (Seminars in Interventional Radiology, 2021)
Cerebrovascular injury is a potentially devastating outcome following craniofacial trauma. Interventional radiologists play an important role in detecting, grading, and treating the different types of vascular injury. Computed tomography angiography plays a significant role in the detection of these injuries. Carotid-cavernous fistulas, extra-axial hematomas, pseudoaneurysms, and arterial lacerations are rare vessel injuries resulting from craniofacial trauma. If left untreated, these injuries can lead to vessel rupture and hemorrhage into surrounding areas. Acute management of these vessel injuries includes early identification with angiography and treatment with endovascular embolization. Endovascular therapy resolves vessel abnormalities and reduces the risk of vessel rupture and associated complications.
Keywords: carotid-cavernous fistulas; extra-axial hematomas; pseudoaneurysms; arterial dissections; craniofacial trauma; interventional radiology